Republic of Poland : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Poland. (IMF Staff Country Reports; Country Report ;, 2022)
The Polish economy has rebounded strongly, with policy actions limiting the damage from the pandemic-induced recession by supporting employment and avoiding unnecessary bankruptcies. While the pandemic continues to take a toll on lives, the economy has been less impacted by successive waves of the pandemic.